A Systematic Review and Meta‐Analysis: Timing of Elective Removal of Tympanostomy Tubes. (29th December 2021) - Tan, Grace X.; Hamilton, Andrew; MacArthur, Carol J.
Abstract : Objective(s): Tympanostomy tube (TT) placement is the most common surgical procedure in children. Less than 10% of TT do not self‐extrude. This study is a systematic review (SR) on elective TT removal in the pediatric population: timing, perforation rates, and role of simultaneous repair. A PICOTS (population, intervention, comparison, outcome, timing, setting) question was formulated: In pediatric patients who have retained TT, what is the preferred time to elective removal of such tubes, and what are the outcomes in terms of perforation rates? Does an intervention at the time of TT removal improve perforation rates? Study Design: Systematic review and meta‐analysis. Methods: We searched four major electronic databases: EMBASE, MEDLINE, CDSR, CCRCT for articles published prior to 02/19/20. EndNote® was used to gather references, review abstracts, and obtain full text articles. Inclusion criteria were studies reporting patients aged 0 to 18 years undergoing elective TT removal with follow‐up greater than 3 months. Exclusion criteria included patients >18 years, duplicate patient series, or case series with fewer than five patients. Articles that were not available in English, not available in full text, and those that only addressed long‐acting TT were excluded. Data were pooled and meta‐analysis was conducted to examine how timing of TT removal, patching of the tympanic membrane, or any TM intervention at TT removal affected outcomes. Results: A total of 1, 064 references were found. We identified 63 unique studies for full text review. Of these, 17 were selected for SR. MINORS (Methodological Index for Nonrandomized Studies) scores were low‐revealing high bias among the studies. Reported perforation rates after elective TT removal ranged from 0% to 57%. Four studies had data suitable for comparative meta‐analysis, which showed a significant increase in perforation rates after elective removal of TT after 3 years compared to removal prior to 3 years (OR 2.89; CI 1.78–4.69). No difference in perforation rates were identified when TM intervention vs. no intervention at time of TT removal was performed (six studies: OR 1.21; CI 0.71–2.07). No difference in perforation rates was identified when the type of TM intervention was compared, including freshening of TM edges, to patching with various materials (paper, fat, gelfoam®/gelfilm®, Trichloroacetic acid) (three studies: OR 1.07; CI 0.52–2.19). Conclusion: From the data reviewed in this SR and meta‐analysis, elective TT removal at or prior to 3 years' retention showed decreased perforation rates. However, TM intervention at the time of TT removal was not shown to lower perforation rates. In the absence of tube complications such as granuloma formation, nonfunctional tube, or chronic tube otorrhea, it may be reasonable to wait up to 3 years to electively remove a retained TT. Laryngoscope, 132:2063–2070, 2022